Cooperative Emission of a Pulse Train in an Optically Thick Scattering Medium - Kwong, Chang Chi (2016)
An optically thick cold atomic cloud emits a coherent flash of light in the forward direction when the phase of an incident probe field is abruptly changed. Because of cooperativity, the duration of this phenomena can be much shorter than the excited lifetime of a single atom. Repeating periodically the abrupt phase jump, we generate a train of pulses with short repetition time, high intensity contrast, and high efficiency. In this regime, the emission is fully governed by cooperativity even if the cloud is dilute.